Dampak Pandemi Covid 19 terhadap Tataniaga Hewan Qurban di Jabodetabek: Studi Kasus pada Mahir Farm - P. Sembada; A. Hakim; S. D. S. Andik (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2021)
The Covid 19 pandemic has a broad impact on the agricultural sector. In the livestock sub-sector, there isusually an increase in demand for livestock and livestock products at certain moments, one of which is theEid al-Adha. However, the Eid al-Adha during the pandemic is different from the pre-pandemic period,affecting the demand and supply of qurban animals. This study was conducted to identify the impactof the Covid 19 pandemic on the value chain of the qurban animals. The research performed in-depthinterviews and an online survey with the actors along the chain and 29 Mahir Farm consumers. Theresults showed changes in supply, distribution, marketing, and demand compared to the pre-pandemiccondition. As a response, Mahir Farm improved the sales by using an online mode and created a TebarQurban program. Tebar Qurban is a program to optimize the qurban animals sales in the central ofproduction and suppliers to minimize the transportation cost. The adaptive strategies by improvingonline sales and the Tebar Qurban program’s procurement effectively enhanced the sales of qurbananimals during pandemic Covid 19. The study also confirms that there were changes in the buyingbehavior of qurban animals. Consumers preferred online purchasing compared to coming directly to thequrban stall. The payment system’s ease is the most crucial factor in influencing consumers’ decisions topurchase the qurban animal. This research underlines the importance of adaptive strategies to surviveduring a pandemic.